Isolation and characterization of bacteria from the midgut of the Asian honey bee (Apis cerana indica) - Terd Disayathanoowat (2018)
Aerobic bacteria were isolated from the midgut of Apis cerana indica on five different media. The highest count (5.4 × 107 colony forming units (CFU/g)) was obtained on Eosin methylene blue (EMB) medium. Fifty-eight isolates were purified and identified using biochemical tests, and 16S rRNA gene sequences were analysed. Two groups of Gamma-proteobacteria and Firmicutes were found. The most abundant species were Klebsiella pneumoniae, Enterobacter cloacae and K. oxytoca. To determine their role in nutrition, enzymes produced from the bacterial isolates were assayed. Protease and lipase activities were detected in some bacterial isolates. The assimilation of fourteen carbon substrates was studied. D-mannose and raffinose showed the highest utilization. Paenibacillus larvae, the cause of American foulbrood disease, was inhibited by some members of Klebsiella.